Perspektif Islam Tentang Peran Reward Dan Punishment Dalam Motivasi Belajar Siswa - Mochammad Ramdan Samadi; Mohamad Yudiyanto; Laesti Nurishlah (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This research explores the role of reward and punishment in student learning motivation from an Islamic perspective. In Islam, rewards are promised to individuals who do good deeds, motivating students to behave positively in the hope of obtaining enjoyment in this world and the hereafter. Meanwhile, punishment functions as a warning to those who make mistakes, with the aim of correcting behavior and teaching the consequences of negative actions. However, it is important to pay attention to the limits and principles of justice in administering punishment, according to Islamic teachings. By understanding this concept, educators can use rewards and punishments wisely to encourage students' academic and moral achievements, while still adhering to Islamic values that prioritize kindness, justice and blessings.